Nanopharmaceuticals: principles and applications vol. 2 - Yata, Vinod Kumar; Ranjan, Shivendu; Dasgupta, Nandita; Lichtfouse, Eric 1960- (Environmental chemistry for a sustainable world, 2021)
This book presents the comprehensive description of basic principles, methodologies, similarities and differences of nano-liposomes and -phytosomes. It focuses on the implications of these nano carriers in drug delivery and also includes detailed classification of nanoinonized drug particles, polymeric nanoparticles and hydrophobic nanoparticles. This book concludes with the biological, technical and study-design challenges of Nanopharmaceuticals and presents critical viewpoints of smart DNA nanostructures. The risk factors and regulatory concerns have also been kept in focus and the book includes the toxicity and application of different types of ionic liquids for humans and environment. It also critically describes characteristics, applications and regulatory gaps of nanoparticle-ionic liquid combined systems